2020
DOI: 10.1371/journal.pone.0231489
|View full text |Cite
|
Sign up to set email alerts
|

Women’s education and coverage of skilled birth attendance: An assessment of Sustainable Development Goal 3.1 in the South and Southeast Asian Region

Abstract: The objective of Sustainable Development Goal 3.1 is to reduce the global maternal mortality ratio (MMR) below 70 per 100,000 live births by 2030. One of the indicators for this objective is the proportion of births attended by skilled health attendants (SBA). This study assessed the progress of low-and middle-income countries from South and Southeast Asian (SSEA) region in SBA coverage and evaluated the contribution of women's education in this progression. Methods The Demographic and Health Surveys were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
4
11
0
Order By: Relevance
“…It was further observed that having one's partner attained a higher level of education increases the likelihood of a woman utilising SBA. Women whose partners had higher education, being more likely to utilise the service of skilled birth attendants is consistent with Bhowmik et al [38]. Our finding is probable because most SSA countries are largely patriarchal societies [39,40], hence partners with high education who are aware of the importance of skilled birth attendance can easily induce their wives to utilise the service of SBAs.…”
Section: Plos Onesupporting
confidence: 89%
“…It was further observed that having one's partner attained a higher level of education increases the likelihood of a woman utilising SBA. Women whose partners had higher education, being more likely to utilise the service of skilled birth attendants is consistent with Bhowmik et al [38]. Our finding is probable because most SSA countries are largely patriarchal societies [39,40], hence partners with high education who are aware of the importance of skilled birth attendance can easily induce their wives to utilise the service of SBAs.…”
Section: Plos Onesupporting
confidence: 89%
“…This evidence, together with our findings, suggests that the Colombian health care system urgently needs to shift towards universal coverage and a structural redesign to address these high levels of fragmentation. In line with previous studies, our findings also support the role of maternal education as a determinant of birth outcomes, particularly of low birth weight [14][15][16]. The overall improvement in maternal education between 2008 and 2018 could have contributed to the amplification of the inequalities between the two extremes of the spectrum because less educated mothers in 2018 were a smaller, more disadvantaged and more vulnerable social group than those in 2008.…”
Section: Discussionsupporting
confidence: 91%
“…For example, mothers with lower educational levels tend to have poorer economic conditions and experience greater exposure to stress, which in turn results in a higher likelihood of engaging in risk-taking behaviours such as smoking and alcohol/drug abuse [15]. Less-educated mothers also make, on average, fewer prenatal care visits and are less likely to access skilled birth attendance care during childbirth [16].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been conducted in SA to explore the associated factors of IYCF practices [ 18 , 19 , 20 , 21 , 22 ] and have identified a range of detrimental factors, including but not limited to the place of residence, household wealth status, household income, cultural beliefs, parental education, mother’s age, mother’s occupation, antenatal and postnatal care, child’s age, child’s sex, modes of delivery, place of delivery, and women’s and mother’s exposure to mass media [ 18 , 19 , 20 , 21 , 22 ]. Among all these factors, the role of mother’s education is beneficial to health and nutritional well-being [ 23 , 24 , 25 , 26 , 27 , 28 ]. Some single-country-specific studies also found a positive association between mother’s education and IYCF practices [ 5 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%